Evolutionary melting pots and reproductive isolation: A ring‐shaped diversification of an odorous frog (Odorrana margaratea) around the Sichuan Basin. Issue 23 (22nd November 2018) - Qiao, Liang; Wen, Guannan; Qi, Yin; Lu, Bin; Hu, Junhua; Song, Zhaobin; Fu, Jinzhong
Abstract: Quaternary climatic oscillations and geography are of primary importance in shaping intraspecific genetic diversity. We examined the diversification patterns and inferred processes for the green odorous frog ( Odorrana margaretae ) of western China. Species distribution modelling showed that the species has a continuous circular distribution around the Sichuan Basin while the basin itself is largely uninhabitable. Population genetic and phylogenetic analyses revealed that the species has a ring‐shaped divergent pattern. While the chain of populations around the Basin maintains a mostly gradual and continuous genetic variation, populations between the north and west showed little gene exchange. Two processes, glacial refugial history and geography, likely contributed to the observed patterns. Our genetic clustering analysis revealed two clusters, suggesting two refugial groups among the populations, one from the west and the other from the east. Postglacial expansion may have created two contact zones. One at the south had extensive population admixture and produced a gradual transition between the western and eastern populations. Consequently, this region has the highest genetic diversity and represents an evolutionary "melting pot." In contrast, the second contact zone at the northwestern side of the Basin has limited admixture, suggesting partial reproductive isolation between the northern and western populations. Furthermore, an isolation‐by‐distance analysis revealed a strong correlation (Mantel r = 0.745) between the genetic and geographic distances, when we assumed that populations were connected following the circular distribution without gene flow across the NW contact zone. We also explored alternative explanations, such as a one‐refugium scenario. With its micro‐ring, the green odorous frog is poised to make an excellent model system for understanding the process of speciation.